Systemic Effects of Occlusal Disharmony on Corticosterone Serum Levels in Rattus Norvegicus - Suhartini; Endang Joewarini; Ida Bagus Narmada (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Mastication process occurs over time and it can lead to occlusal reduction of the teeth. Thiscauses reducing occlusal contact of teeth and it will lead to disharmony occlusion disorders. The occlusiondisharmony is recognized by the body as a stressor that systemically affects the homeostasis in the body,especially the production of hormones.Objective: The aim of this study was to determine the systemic effect of occlusal disharmony on corticosteroneserum levels in Rattus norvegicus.Method: The research method of this study used experimental design and conducted among 7 male RattusNorvegicus in each groups. In intervention group, an occlusal reduction was ± 1 mm in all molars andfor control group did not given any intervention. Moreover, at 1st day, 7th day, 14th day and 21st day wastaken 2 cc of blood via infraorbital vein. The measurement of Corticosterone levels used Enzyme LinkedImmunosorbent Assay (ELISA).Result: Anova test results showed that corticosterone levels was significant difference between each groups(p <0.05). Tukey HSD test showed there was a significant difference between intervention group and controlgroup on 1st day, in intervention group on 7th day (p <0.05).Conclusion. The results of this study showed that there were differences of corticosterone serum levelsamong mice who experienced occlusion disharmony so it concluded that the dental occlusion disharmonyhad a systemic impact to corticosterone serum levels in Rattus norvegicus